Informal recyclers' geographies of surviving neoliberal urbanism in Vancouver, BC. (January 2016) - Wittmer, Josie; Parizeau, Kate
Abstract: Based on our study of informal recyclers' experiences of well-being, we draw on "geographies of survival" to understand the challenges that these informal workers experience in a context of urban change in Vancouver, BC. This concept explains that impoverished city residents construct pathways through the urban landscape that provide shelter, access to food, spaces of safety, and community. Informal recyclers' geographies of survival are connected with urban inequality and are exacerbated by neoliberal trends in the governance of Vancouver's physical, social, and political spaces. We observe that certain users and uses of public space are defined as disorderly or illegitimate, the poor are pushed to the margins of society, and rhetorical urban revitalization and "greening" agendas are prioritized over the needs of the poor in policy making. However, neoliberal trends are inherently contradictory and can change based on local contestation and opposition. Geographies of survival are therefore an important mechanism through which informal recyclers can reclaim city spaces as they resist spatial restrictions and work to maintain their access to necessary resources. We conclude that the geographies of survival lens provides an important perspective on urban power relationships and their spatial dynamics in contemporary Vancouver. Highlights: Informal recyclers' geographies of survival are exacerbated by neoliberal trends. Neoliberal urbanism reduces access to public spaces, and criminalizes "disorder". Informal recyclers' access to spaces of survival is constrained in Vancouver. Through their survival activities, informal recyclers can reclaim city spaces.